Guidelines for Service Quality Improvement for a Commercial Bank in Sriracha Branch, Chonburi Province - เลิศพุทธิรักษ์ ศรัณยา; ท่าหิน วรรณวิสา (Journal of KMITL Business school, 2019)
The purpose of this research is to study the service quality affecting the loyalty of service user of a commercial bank in Sriracha branch, Chonburi Province and to study openions of employee on service quality, problem and obstracle in providing service and suggessions for improving the service of the bank. Two research methods are used in this study, quatitative method by collecting quationaires with sample of 379 peple and qualitative method wiht in-dept interview of 6 bank officers. The result of quantitative research showed that the service quality factors had an effect on the loyalty of the users with a statistical significance level of 0.05. The qualitative research has shown the opinions of the staff on the problems and obstracles in providing services to customers are mostly as following: insufficient number of parking spaces and waiting areas for services as well as lack of toilet for customers. Service improvement should be as follows: employees must service every customer quality wihtout discrimination, sincere and fast service with a smile must be provided, the personal details of customers, such as client’s name must be recognized, answering of client’ s quation in a timely manner and using social media for communications with the customers to give them understanding and confidence in using services of the bank, must be done.